A Diagnostic Survey of Aborted Equine Fetuses and Stillborn Premature Foals in Denmark - Agerholm, Jørgen Steen; Klas, Eva-Maria; Damborg, Peter; Borel, Nicole; Pedersen, Hanne Gervi; Christoffersen, Mette (Frontiers in Veterinary Science, 2021)
Background: Loss of pregnancy in mares can have many different causes, including both infectious and non-infectious conditions. Extrapolation of findings from other studies is often uncertain as the significance of each cause varies across regions. Causes of pregnancy loss in mares have never been thoroughly studied in Denmark, so a prospective cross-sectional cohort study targeting the entire Danish population of pregnant mares was performed over a period of 13 months to obtain knowledge of the significance of individual causes. Fifty aborted or prematurely delivered stillborn fetuses were submitted for necropsy and examined by a panel of diagnostic laboratory methods. Results: Overall, a cause of fetal loss was established for 72% of the examined cases. Most cases (62%) were lost due to a non-infectious cause, of which obstruction of the feto-placental blood circulation due to severe torsion of the umbilical cord was most prevalent. Pregnancy loss due to a variety of opportunistic bacteria, including bacteria not previously associated with abortion in mares, accounted for 12%, while equid alphaherpesvirus (EHV) type 1 was the cause of pregnancy loss in 8% of the cases. EHV type 4 and Chlamydiaceae species were identified in some cases, but not regarded as the cause of fetal loss. Conclusion: Umbilical cord torsion was found to be the most prevalent cause of fetal loss in Danish mares, while infectious causes such as EHV type 1 and streptococci only accounted for a minor proportion of the losses. The study highlights the need for defined criteria for establishing an abortion diagnosis in mares, particularly in relation to EHV types 1 and 4.